2020
DOI: 10.21873/anticanres.14063
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related Adverse Effects and Outcome of Patients With Cancer Treated With Immune Checkpoint Inhibitors

Abstract: Fiala et al: Immune-related Adverse Effects and Outcome of Patients Treated With Immunotherapy (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
(63 reference statements)
2
21
0
Order By: Relevance
“…the development of irAEs) is present in patients treated with immune checkpoint inhibitors. These irAEs may involve the dermatologic, gastrointestinal and endocrine systems ( 28 , 29 ). In this study, various irAEs were reported in 57 out of 124 patients, with skin disorders the most common ( n = 22), followed by thyroid dysfunction ( n = 21) and vitiligo ( n = 14) ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the development of irAEs) is present in patients treated with immune checkpoint inhibitors. These irAEs may involve the dermatologic, gastrointestinal and endocrine systems ( 28 , 29 ). In this study, various irAEs were reported in 57 out of 124 patients, with skin disorders the most common ( n = 22), followed by thyroid dysfunction ( n = 21) and vitiligo ( n = 14) ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk for developing dermatologic irAEs was 2.3 in patients with various cancers treated with nivolumab, and vitiligo is characteristically reported in trials investigating the use of these inhibitors in malignant melanoma ( 30 ). In addition, dermatologic irAEs are reportedly associated with a higher response rate and improved survival in patients with melanoma treated with PD-1 inhibitors, including nivolumab ( 28 , 29 ). Generally, dermatologic irAEs associated with nivolumab treatment are primarily low grade and manageable with established safety guidelines ( 7 , 8 ); therefore, the development of dermatologic irAEs seems to have a clinical benefit ( 29 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, immune-checkpoint inhibitors can induce immunerelated adverse events (irAEs) including rash, colitis, hepatitis, endocrinopathies, and pneumonitis (2,3). IrAEs have been associated with patient characteristics, efficacy and total number of doses of PD-1 inhibitors (4)(5)(6). In patients with various malignancies treated with immunecheckpoint inhibitors, irAEs are associated with better survival (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…A 3-year follow-up study of 126 squamous cell carcinoma of the head and neck (SCCHN) patients receiving anti-PD-1/L1 therapy demonstrated that SMARCA4 mutation and/or frameshift were more frequently observed in responders than nonresponders 67 . Consistently, a case report of thoracic sarcoma showed that SMARCA4 deficiency resulted in notable clinical response to Nivolumab (anti-PD-1) treatment 68 . Of note, in a small cohort study, four small-cell carcinomas of the ovary, hypercalcemic type (SCCOHT) patients showed a notable response to anti-PD-1 immunotherapy.…”
Section: Smarca4/brg1mentioning
confidence: 71%